Seroprevalence of Getah virus in pigs in Southeast China determined with a recombinant Cap protein-based indirect ELISA - Lan, Jianhui; Duan, Leilei; Liu, Xuya; Zhou, Yao; Zeng, Botao; Chen, Siya; Ye, Yu; Huang, Dongyan; Wan, Gen; Zhang, Fanfan; Song, Deping (Frontiers in Microbiology, 2025)
Getah virus (GETV) is a mosquito-borne virus with a broad host range, including mosquitoes and various animals such as pigs, horses, goats, cattle, boars, and blue foxes. In pigs, GETV can cause fever, abortion and reproductive disorders in sows, as well as fever, tremors, and diarrhea in piglets, posing a serious threat to the pig production industry. However, there are few reports on the epidemiology of GETV in China, and reliable diagnostic kits for large-scale detection of GETV antibodies are lacking. Therefore, this study aimed to establish a rapid, sensitive and suitable GETV antibody detection assay for clinical detection. We expressed the recombinant protein Cap in Escherichia coli by constructing a recombinant plasmid, pET-32a-Cap, which contained a His tag and the GETV-Cap domain. The expression of the recombinant protein was achieved in the supernatant following bacterial lysis by optimizing the culture temperature and duration for Escherichia coli. The recombinant Cap protein was successfully purified via a nickel affinity column, which was used for develop an indirect ELISA method (rCap-ELISA). Following optimization of the rCap-ELISA reaction conditions, a cutoff value of 0.45 was established with 100 swine serum samples analyzed by indirect immunofluorescence (IFA). The overall coincidence rate between rCap-ELISA and IFA was 95.83%, with a 94.03% sensitivity and 100.00% specificity. IgG antibodies against GETV were subsequently detected in 2,102 serum samples from pig farms in Jiangxi and Fujian provinces via the rCap-ELISA method, and the positive rates were 63.36% (1,102/1739) and 37.1% (137/363), respectively. The findings suggest that the indirect ELISA method (rCap-ELISA) is a reliable, accurate, and cost-effective way to detect IgG antibodies against GETV in pigs. This technique is valuable for understanding the dynamics of GETV transmission and for preventing GETV epidemics in pigs.